Impact of Organizational and Family Support on Work-Life Balance: An Empirical Research - Banik, Subrata; Akter, Kaniz Marium; Molla, Mohammad Shahansha (Business Perspective Review, 2022)
Purpose: Aim of this study is to examine the impact of organization and family support on an individual’s work-life balance (WLB in the context of higher educational institutes (HEIs) in Bangladesh. The theoretical basis of the study is grounded on the work/family border theory of Clark (2000). Methods: The study was conducted with a sample of 198 academicians of the (HEIs) in Bangladesh. A self-administered questionnaire was used for data collection. SPSS version 21 and SmartPLS 3.0 software were used for data analysis. A measurement model was analyzed for assessing the reliability and validity of the research instrument. The partial least squares structural equation model (PLS-SEM) was applied for testing the hypothesized model of the study. Results: The results reveal that organizational support (β = 0.404) and family support (β = 0.269) significantly (p<0.05) influence work-life balance with a variance (R2) of 32.1%. Implications: This study exposed the organizational roles in managing the conflicts of people’s personal life and professional life. Findings would inspire the authorities to formulate employee-friendly organizational strategies and design WLB programs in assisting employees to manage their overall life both in the work and family domains. Limitations: The research was limited to HEIs in Bangladesh which restricts the generalizability of its results.